Monolithic catalyst for methane catalytic combustion and preparation method thereof

By forming a TiO2 coating on the honeycomb support and introducing 3-(trifluoroacetamide)pyrrolidine hydrochloride, a perovskite type metal oxide catalyst was prepared, which solved the problem of insufficient low-temperature activity of perovskite type catalysts, and achieved the goal of realizing the It has efficient methane catalytic combustion and long-term stability, and is suitable for low-temperature catalytic methane.

CN119237027AActive Publication Date: 2025-01-03CHINA PETROLEUM & CHEMICAL CORP +1

Patent Information

Application Number
CN202310792304.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-30
Publication Date
2025-01-03
Estimated Expiration
2043-06-30

AI Technical Summary

Technical Problem

The existing perovskite catalysts have poor catalytic activity at low temperatures, which limits their application in methane catalytic combustion. In addition, precious metal catalysts are costly and have poor stability, and the preparation of non-precious metal catalysts is complex and difficult to apply on a large scale.

Method used

By forming a TiO2 coating on a honeycomb support and adding 3-(trifluoroacetamide)pyrrolidine hydrochloride to the active metal salt solution, the perovskite metal oxide monolithic catalyst is prepared to enhance electron transfer capacity and Redox capacity, improve low-temperature catalytic activity, and improve catalyst performance through the bridge structure of TiO2 and ABO3.

Benefits of technology

It achieves efficient catalytic methane combustion at low temperatures, T90≤500℃, and maintains good activity during long-term use, reduces the reaction temperature and improves the low-temperature catalytic activity and stability of the catalyst.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to a preparation method of a monolithic catalyst for methane catalytic combustion, which comprises the following steps: dipping a honeycomb carrier in titanium dioxide sol, taking out, drying, and roasting to obtain a carrier with a TiO2 coating; the carrier with the TiO2 coating is soaked in an active metal salt solution, 3-(trifluoroacetamido) pyrrolidine hydrochloride is added into the active metal salt solution, active metal is perovskite type metal composite oxide, the structural general formula is ABO, the carrier is taken out, dried and roasted, and the monolithic catalyst is obtained. The monolithic catalyst provided by the invention is used for catalytic combustion of methane, T90 is less than or equal to 500 DEG C, and the monolithic catalyst has the advantages of high low-temperature catalytic activity, good activity retention after long-term use and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of waste gas treatment, and in particular relates to an integral catalyst for catalytic combustion of methane and a preparation method thereof. Background Art

[0002] Methane is the second largest greenhouse gas, accounting for about 20% of global greenhouse gas emissions and contributing about a quarter to global warming. Methane molecules are stable tetrahedral structures and can be decomposed at temperatures above 1500°C. Methane catalytic combustion technology is an effective treatment method to replace traditional thermal combustion methods, and the key lies in the catalyst. Methane catalytic combustion catalysts are roughly divided into two categories according to the active components: precious metal catalysts and non-precious metal catalysts. Among them, although precious metal catalysts have good low-temperature ignition activity and anti-poisoning ability, their large-scale production and application are subject to certain constraints due to factors such as poor high-temperature stability and high cost of precious metals. Non-precious metal catalysts are mainly divided into perovskite-type metal composite oxides and hexaaluminate-type metal composite oxides (the disadvantage is that the product preparation is relatively difficult) and other metal oxides (the disadvantage is that they are easy to sinter at high temperatures). Perovskite-type catalysts can overcome the above disadvantages and have the characteristics of moderate ignition temperature, simple and easy preparation process, low cost, and strong resistance to high-temperature sintering, but poor low-temperature activity limits their development and application.

[0003] The monolithic catalyst has a regular pore structure and is easy to load catalytically active components. It can reduce the reaction pressure, optimize the operating conditions, and save operating costs. It is widely used in the research and development of methane catalytic combustion catalysts.

[0004] CN106944093A discloses a perovskite-type honeycomb monolithic methane catalytic combustion catalyst and a preparation method thereof, wherein the catalyst comprises an active component and an inert honeycomb carrier, wherein the active component comprises rare earth metal elements, alkaline earth metal elements, and transition metal elements, and the carrier is a cordierite-based honeycomb carrier, a mullite-based honeycomb carrier, or an alumina-based honeycomb carrier. The preparation method comprises the following steps: (1) Preparation of an active component precursor solution: preparing an aqueous solution of a soluble metal salt according to the molar ratio of the metal elements required by the active component, i.e., an active component precursor solution, wherein the total molar concentration of metal ions is 1.0-2.0 mol / L; (2) Loading of the active component: impregnating the inert honeycomb carrier with the active component precursor solution, and drying and calcining the inert honeycomb carrier after impregnation to obtain the perovskite-type honeycomb monolithic methane catalytic combustion catalyst. The calcination temperature is 750-850°C and the time is 2-3h. At a space velocity of 15000h -1 Under the conditions of CH4 3.0% (v / v), T 10 >500℃,T 90 >650℃, low temperature catalytic activity needs to be improved.

[0005] CN103831095A discloses an integral metal composite catalyst for catalytic combustion of methane and a preparation method thereof. The integral metal composite catalyst is formed by coating the surface of a porous substrate with perovskite, wherein the general structural formula of the perovskite is: ABO3, the metal element A is one or more of group ⅡA or lanthanide elements, and the metal element B is one or more of transition metals. The preparation method comprises: (1) pretreatment of a porous substrate: immersing the porous substrate in ammonia water and cerium nitrate aqueous solution in turn, taking it out, drying it and calcining it; (2) preparing a pseudo-boehmite aqueous solution and a soluble salt solution of perovskite, and mixing the two to obtain a precursor aqueous solution; (3) adding an organic complexing agent to the precursor aqueous solution, stirring it, and dripping nitric acid to obtain an aluminum sol; (4) immersing the pretreated porous substrate in the aluminum sol, drying it and calcining it, wherein the porous substrate is placed in the aluminum sol for 10-720 minutes, removing excess liquid, drying it at 50-140°C for 3-16 hours, then calcining it at 300-600°C for 2-6 hours, and finally calcining it at 600-1300°C for 2-6 hours, thereby obtaining the integral metal composite catalyst. The patent is prepared by first uniformly dispersing the metal elements in the perovskite in the aluminum sol, then complexing with the organic complexing agent, and finally indirectly adsorbing them on the porous matrix. -1 Under the conditions of CH4 concentration of 3.5% (v / v), T90 ≥ 520℃, the low-temperature catalytic activity needs to be further improved. Summary of the invention

[0006] In view of the shortcomings of the prior art, the present invention provides an integral catalyst for catalytic combustion of methane and a preparation method thereof. The integral catalyst provided by the present invention is used for catalytic combustion of methane. 90 ≤500℃, it has the advantages of high low-temperature catalytic activity and good activity retention in long-term use.

[0007] The present invention provides a method for preparing a monolithic catalyst for catalytic combustion of methane, comprising the following steps:

[0008] (1) dipping the honeycomb carrier into titanium dioxide sol, taking it out, drying it, and calcining it to obtain a carrier with a TiO2 coating;

[0009] (2) The carrier with the TiO2 coating is immersed in an active metal salt solution, to which 3-(trifluoroacetamido)pyrrolidine hydrochloride is added, wherein the active metal is a perovskite-type metal composite oxide with a general structural formula of ABO3, and then taken out, dried, and calcined to obtain a monolithic catalyst.

[0010] In the present invention, the honeycomb carrier described in step (1) is a honeycomb ceramic carrier or a metal honeycomb carrier, specifically at least one of cordierite honeycomb ceramics, mullite honeycomb ceramics, stainless steel foil, FeCrAl, etc., with a mesh size of 300-500 meshes.

[0011] In the present invention, the titanium dioxide sol described in step (1) is conventional and can be obtained by commercial purchase or self-production, preferably nano titanium dioxide sol, with a particle size of 5-50nm. Further, the preferred preparation method is: (a) glacial acetic acid, anhydrous ethanol and deionized water are mixed at room temperature to obtain solution A, wherein the mass ratio of deionized water, glacial acetic acid and anhydrous ethanol is 5:1-8:3-10; (b) butyl titanate and anhydrous ethanol are mixed at room temperature to obtain solution B, wherein the mass ratio of butyl titanate to anhydrous ethanol is 1:0.5-2; (c) solution B is added dropwise to solution A under vigorous stirring, the mass ratio of solution A to solution B is 1:0.5-5, the dropping rate is 10-25mL / min, after the dropwise addition is completed, stirring at room temperature for 1-3h to obtain titanium dioxide sol, and the stirring rate is 200-500r / min.

[0012] In the present invention, step (1) is to immerse the honeycomb carrier in titanium dioxide sol for 2-5 minutes.

[0013] In the present invention, the drying temperature in step (1) is 80-120° C., the drying time is 12-24 hours, and the roasting temperature is 650-800° C., the roasting time is 3-6 hours.

[0014] In the present invention, the mass content of 3-(trifluoroacetamido)pyrrolidine hydrochloride in the active metal salt solution in step (2) is 1%-10%, preferably 3%-5%.

[0015] In the present invention, the active metal described in step (2) is a non-precious metal, specifically including two kinds of metals A and B, wherein A is generally at least one of La, Ce, etc., and B is generally at least one of Fe, Co, Ni, Mn, etc., wherein the molar ratio of active metals A and B is 1:1. The active metal salt solution is generally a soluble metal salt thereof, such as one or more of nitrates, chlorides, etc., and the concentration of the active metal salt solution is generally 1 to 3 mol / L.

[0016] In the present invention, in step (2), the carrier with the TiO2 coating is immersed in an active metal salt solution for 2-5 minutes.

[0017] In the present invention, the drying temperature in step (2) is 80-120° C., and the drying time is 12-24 hours; the roasting temperature is 650-800° C., and the roasting time is 3-6 hours.

[0018] The monolithic catalyst for catalytic combustion of methane described in the present invention is a monolithic catalyst in which a perovskite metal oxide (ABO3) is loaded on a honeycomb carrier with a TiO2 coating, wherein the chlorine content is 0.001%-0.05% and the active metal content is 3%-8% based on the catalyst mass.

[0019] The present invention also provides an application of the prepared methane catalytic combustion catalyst, which is used for the catalytic combustion of methane at low temperature and has the advantages of high low-temperature catalytic activity, good activity retention during long-term use, etc.

[0020] In the application of the present invention, at a volume space velocity of 10000h -1 ~30000h -1 , under the condition of methane volume concentration of 1% to 3.5%, T 90 ≤500℃.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] (1) In view of the problem of poor low-temperature activity of perovskite-type catalysts, the inventors of the present application introduced 3-(trifluoroacetamido)pyrrolidine hydrochloride into an active metal salt solution to prepare a perovskite-type metal oxide monolithic catalyst, which can establish a bridge between TiO2 and ABO3 through a carbonyl group, enhance the electron transfer ability between the two, and increase the migration rate of bulk lattice oxygen to the catalyst surface, thereby improving the catalytic activity and reducing the reaction temperature. At the same time, the halogen functional group in 3-(trifluoroacetamido)pyrrolidine hydrochloride has good electrical conductivity, which helps to improve the redox ability of ABO3, thereby improving the low-temperature catalytic activity.

[0023] (2) The introduction of 3-(trifluoroacetamido)pyrrolidine hydrochloride enhances the strong interaction between the active metal and the support, which helps to maintain the catalyst activity.

[0024] (3) After coating and calcination, the titanium dioxide sol forms a TiO2 coating on the surface of the honeycomb carrier, which can generate electron cloud entanglement with the active component ABO3, inhibit the migration and agglomeration of the active component on the carrier surface, and help to improve and maintain good low-temperature catalyst activity. DETAILED DESCRIPTION

[0025] The technical solution of the present invention and its effects are further illustrated by the following examples. The examples are implemented on the premise of the technical solution of the present invention, and detailed implementation methods and specific operation processes are given, but the protection scope of the present invention is not limited to the following examples.

[0026] The experimental methods in the following examples, unless otherwise specified, are all conventional methods in the art. The experimental materials used in the following examples, unless otherwise specified, can all be purchased from biochemical reagent stores.

[0027] In the embodiment of the present invention, T 90 Indicates the methane ignition temperature when the methane conversion rate reaches 90%.

[0028] Example 1

[0029] (1) Immerse a 400-mesh cordierite honeycomb ceramic carrier in commercial titanium dioxide sol at room temperature for 3 minutes, with a titanium dioxide particle size of 10 nm. After being taken out, dry it at 100°C for 12 hours and calcine it at 650°C for 4 hours to obtain a carrier with a TiO2 coating;

[0030] (2) Prepare an active metal salt solution with a concentration of 2.5 mol / L, wherein the metal salt A is La(NO3)3·6H2O, and the metal salts B are Fe(NO3)3·9H2O and Ni(NO3)2·6H2O, wherein the molar ratio of A to B is 1:1, and the molar ratio of Ni to Fe is 0.2:0.8. Add 3-(trifluoroacetamido)pyrrolidine hydrochloride to the active metal salt solution at a mass content of 3.5%, immerse the support with the TiO2 coating in the active metal salt solution for 3 min, take out and dry at 100°C for 12 h, and calcine at 700°C for 4 h to obtain LaNi 0.2 Fe 0.8 O3 / TiO2 monolithic catalyst: Based on the mass of the catalyst, the chlorine content is 0.026% and the active metal content is 4.8%.

[0031] The activity evaluation results of the prepared catalyst are as follows:

[0032] At a methane volume concentration of 3.5% and a volume space velocity of 25000 h -1 Under the condition, T 90 The methane removal rate was 88.6% after continuous operation at 485°C for 100 hours.

[0033] Example 2

[0034] (1) Immerse a 400-mesh cordierite honeycomb ceramic carrier in commercial titanium dioxide sol at room temperature for 4 minutes, with a titanium dioxide particle size of 20 nm. After being taken out, dry it at 110°C for 12 hours, and calcine it at 700°C for 4 hours to obtain a carrier with a TiO2 coating;

[0035] (2) Prepare an active metal salt solution with a concentration of 3 mol / L, wherein the metal salt A is La(NO3)3·6H2O, and the metal salts B are Fe(NO3)3·9H2O and Ni(NO3)2·6H2O, wherein the molar ratio of A to B is 1:1, and the molar ratio of Ni to Fe is 0.2:0.8. Add 3-(trifluoroacetamido)pyrrolidine hydrochloride at a mass content of 4% to the active metal salt solution, immerse the support with the TiO2 coating in the active metal salt solution for 4 minutes, take out and dry at 110°C for 12 hours, and calcine at 700°C for 4 hours to obtain LaNi 0.2 Fe 0.8 O3 / TiO2 monolithic catalyst: Based on the mass of the catalyst, the chlorine content is 0.045% and the active metal content is 5.8%.

[0036] The activity evaluation results of the prepared catalyst are as follows:

[0037] At a methane volume concentration of 3.5% and a volume space velocity of 25000 h -1 Under the condition, T 90 The methane removal rate was 86.7% when the temperature was 486°C and the temperature was 486°C for 100 hours.

[0038] Example 3

[0039] (1) Immerse a 300-mesh cordierite honeycomb ceramic carrier in commercial titanium dioxide sol at room temperature for 4 minutes, with a titanium dioxide particle size of 20 nm. After being taken out, dry it at 80°C for 24 hours, and calcine it at 800°C for 3 hours to obtain a carrier with a TiO2 coating;

[0040] (2) An active metal salt solution with a concentration of 1 mol / L was prepared, wherein the metal salt A was La(NO3)3·6H2O, and the metal salts B were Fe(NO3)3·9H2O and Ni(NO3)2·6H2O, wherein the molar ratio of A to B was 1:1, and the molar ratio of Ni to Fe was 0.2:0.8. 3-(Trifluoroacetamido)pyrrolidine hydrochloride was added to the active metal salt solution at a mass content of 3%, and the support with the TiO2 coating was immersed in the active metal salt solution for 2 min, taken out and dried at 80°C for 24 h, and calcined at 800°C for 3 h to obtain LaNi 0.2 Fe 0.8 O3 / TiO2 monolithic catalyst: Based on the mass of the catalyst, the chlorine content is 0.019% and the active metal content is 3.4%.

[0041] The activity evaluation results of the prepared catalyst are as follows:

[0042] At a methane volume concentration of 3.5% and a volume space velocity of 25000 h -1 Under the condition, T 90The methane removal rate was 87.8% after continuous operation at 488°C for 100 hours.

[0043] Example 4

[0044] (1) Immerse a 400-mesh cordierite honeycomb ceramic carrier in commercial titanium dioxide sol at room temperature for 3 minutes, with a titanium dioxide particle size of 10 nm. After being taken out, dry it at 100°C for 12 hours and calcine it at 650°C for 4 hours to obtain a carrier with a TiO2 coating;

[0045] (2) Prepare an active metal salt solution with a concentration of 2.5 mol / L, wherein the metal salt A is Ce(NO3)3·6H2O, and the metal salts B are Fe(NO3)3·9H2O and Ni(NO3)2·6H2O, wherein the molar ratio of A to B is 1:1, and the molar ratio of Ni to Fe is 0.2:0.8. Add 3-(trifluoroacetamido)pyrrolidine hydrochloride to the active metal salt solution at a mass content of 3.5%, immerse the support with the TiO2 coating in the active metal salt solution for 3 min, take out and dry at 100°C for 12 h, and calcine at 700°C for 4 h to obtain CeNi 0.2 Fe 0.8 O3 / TiO2 monolithic catalyst: Based on the mass of the catalyst, the chlorine content is 0.028% and the active metal content is 4.9%.

[0046] The activity evaluation results of the prepared catalyst are as follows:

[0047] At a methane volume concentration of 3.5% and a volume space velocity of 25000 h -1 Under the condition, T 90 The methane removal rate was 88.5% after continuous operation at 487°C for 100 hours.

[0048] Example 5

[0049] (1) Immerse a 400-mesh cordierite honeycomb ceramic carrier in commercial titanium dioxide sol at room temperature for 3 minutes, with a titanium dioxide particle size of 10 nm. After being taken out, dry it at 100°C for 12 hours and calcine it at 650°C for 4 hours to obtain a carrier with a TiO2 coating;

[0050] (2) An active metal salt solution with a concentration of 2.5 mol / L was prepared, wherein the metal salt A was La(NO3)3·6H2O, and the metal salts B were Mn(NO3)2·6H2O and Co(NO3)2·6H2O, wherein the molar ratio of A to B was 1:1, and the molar ratio of Co to Mn was 0.2:0.8. 3-(Trifluoroacetamido)pyrrolidine hydrochloride was added to the active metal salt solution at a mass content of 3.5%, and the support with the TiO2 coating was immersed in the active metal salt solution for 3 min, and then taken out and dried at 100°C for 12 h, and calcined at 700°C for 4 h to obtain LaCo0.2 Mn 0.8 O3 / TiO2 monolithic catalyst: Based on the mass of the catalyst, the chlorine content is 0.03% and the active metal content is 4.7%.

[0051] The activity evaluation results of the prepared catalyst are as follows:

[0052] At a methane volume concentration of 3.5% and a volume space velocity of 25000 h -1 Under the condition, T 90 The methane removal rate was 88.2% after continuous operation at 481°C for 100 hours.

[0053] Example 6

[0054] (1) Immerse a 400-mesh cordierite honeycomb ceramic carrier in commercial titanium dioxide sol at room temperature for 3 minutes, with a titanium dioxide particle size of 10 nm. After being taken out, dry it at 100°C for 12 hours and calcine it at 650°C for 4 hours to obtain a carrier with a TiO2 coating;

[0055] (2) Prepare an active metal salt solution with a concentration of 2.5 mol / L, wherein the metal salt A is La(NO3)3·6H2O, and the metal salts B are Fe(NO3)3·9H2O and Ni(NO3)2·6H2O, wherein the molar ratio of A to B is 1:1, and the molar ratio of Ni to Fe is 0.2:0.8. Add 3-(trifluoroacetamido)pyrrolidine hydrochloride at a mass content of 1.5% to the active metal salt solution, immerse the support with the TiO2 coating in the active metal salt solution for 3 minutes, take out and dry at 100°C for 12 hours, and calcine at 700°C for 4 hours to obtain LaNi 0.2 Fe 0.8 O3 / TiO2 monolithic catalyst: Based on the mass of the catalyst, the chlorine content is 0.015% and the active metal content is 3.2%.

[0056] The activity evaluation results of the prepared catalyst are as follows:

[0057] At a methane volume concentration of 3.5% and a volume space velocity of 25000 h -1 Under the condition, T 90 The methane removal rate was 85.7% after continuous operation at 496°C for 100 hours.

[0058] Example 7

[0059] The same as Example 1, except that: the preparation method of titanium dioxide sol is: (a) glacial acetic acid, anhydrous ethanol and deionized water are mixed at room temperature to obtain solution A, wherein the mass ratio of deionized water, glacial acetic acid and anhydrous ethanol is 5:6:5; (b) butyl titanate and anhydrous ethanol are mixed at room temperature to obtain solution B, wherein the mass ratio of butyl titanate to anhydrous ethanol is 1:1.5; (c) solution B is added dropwise to solution A under vigorous stirring, the mass ratio of solution A to solution B is 1:2, the dropping rate is 20 mL / min, and after the dropping is completed, the titanium dioxide sol is obtained by stirring at room temperature for 2 h, and the stirring rate is 300 r / min.

[0060] At a methane volume concentration of 3.5% and a volume space velocity of 25000 h -1 Under the condition, T 90 The methane removal rate was 89.8% after continuous operation at 483°C for 100 hours.

[0061] Example 8

[0062] Same as Example 1, except that the honeycomb substrate is a FeCrAl metal honeycomb substrate.

[0063] At a methane volume concentration of 1.5% and a volume space velocity of 25000 h -1 Under the condition, T 90 The methane removal rate was 85.3% after continuous operation at 495°C for 100 hours.

[0064] Comparative Example 1

[0065] Same as Example 1, except that 3-(trifluoroacetamido)pyrrolidine hydrochloride was not added in step (1). -1 Under the condition, T 90 The methane removal rate is 80.7% when the temperature is 553°C and the temperature is 553°C for 100 hours.

[0066] Comparative Example 2

[0067] Same as Example 1, except that: in step (1), γ-Al2O3 is used instead of TiO2 sol. At a methane volume concentration of 3.5% and a volume space velocity of 25000 h -1 Under the condition, T 90 The temperature was 534°C. The methane removal rate was 82.7% after continuous operation at 534°C for 100 hours.

[0068] Comparative Example 3

[0069] The same as Example 1, except that: in step (2), an active metal salt solution with a concentration of 2.5 mol / L is prepared, wherein the metal salt A is Sr(NO3)2, and the metal salts B are Fe(NO3)3·9H2O and Ni(NO3)2·6H2O, wherein the molar ratio of A to B is 1:1, and the molar ratio of Ni to Fe is 0.2:0.8. In a methane volume concentration of 3.5% and a volume space velocity of 25000h -1 Under the condition, T 90 The temperature was 523°C. The methane removal rate was 81.6% after continuous operation at 523°C for 100 hours.

Claims

1. A method for preparing a monolithic catalyst for catalytic combustion of methane, characterized in that The steps include: (1) The honeycomb carrier is immersed in titanium dioxide sol, taken out, dried and calcined to obtain a carrier with a TiO2 coating; (2) The carrier with the TiO2 coating is immersed in an active metal salt solution to which 3-(trifluoroacetamido)pyrrolidine hydrochloride is added, wherein the active metal is a perovskite-type metal composite oxide with the general structural formula ABO3. After being taken out, the carrier is dried and calcined to obtain an integral catalyst.

2. The method according to claim 1, characterized in that: The honeycomb carrier described in step (1) is a honeycomb ceramic carrier or a metal honeycomb carrier, preferably at least one of cordierite honeycomb ceramic, mullite honeycomb ceramic, stainless steel foil, and FeCrAl, with a mesh size of 300-500 meshes.

3. The method according to claim 1, characterized in that: The titanium dioxide sol described in step (1) is obtained by commercial purchase or self-production, preferably nano-titanium dioxide sol with a particle size of 5-50 nm.

4. The method according to claim 1 or 3, characterized in that: The preparation method of titanium dioxide sol is as follows: (a) mixing glacial acetic acid, anhydrous ethanol and deionized water at room temperature to obtain solution A, wherein the mass ratio of deionized water, glacial acetic acid and anhydrous ethanol is 5:1-8:3-10; (b) mixing butyl titanate and anhydrous ethanol at room temperature to obtain solution B, wherein the mass ratio of butyl titanate to anhydrous ethanol is 1:0.5-2; (c) adding solution B dropwise into solution A under vigorous stirring, wherein the mass ratio of solution A to solution B is 1:0.5-5, the dropping rate is 10-25 mL / min, and after the dropping is completed, stirring at room temperature for 1-3 h to obtain titanium dioxide sol, and the stirring rate is 200-500 r / min.

5. The method according to claim 1, characterized in that: Step (1) is to immerse the honeycomb carrier in titanium dioxide sol for 2-5 minutes.

6. The method according to claim 1, characterized in that: In step (1), the drying temperature is 80-120° C., and the drying time is 12-24 hours; the roasting temperature is 650-800° C., and the roasting time is 3-6 hours.

7. The method according to claim 1, characterized in that: The mass content of 3-(trifluoroacetamido)pyrrolidine hydrochloride in the active metal salt solution in step (2) is 1%-10%, preferably 3%-5%.

8. The method according to claim 1, characterized in that: The active metal described in step (2) is a non-precious metal, specifically including two types of metals A and B, wherein A is at least one of La and Ce, and B is at least one of Fe, Co, Ni, and Mn, wherein the molar ratio of the active metals A and B is 1:

1.

9. The method according to claim 1 or 8, characterized in that: The active metal salt solution in step (2) is a soluble metal salt, preferably one or more of nitrates and chlorides, and the concentration of the active metal salt solution is 1 to 3 mol / L.

10. The method according to claim 1, characterized in that: Step (2) The carrier with the TiO2 coating is immersed in an active metal salt solution for 2-5 minutes.

11. The method according to claim 1, characterized in that: The drying temperature in step (2) is 80-120° C., and the drying time is 12-24 hours; the roasting temperature is 650-800° C., and the roasting time is 3-6 hours.

12. A monolithic catalyst for catalytic combustion of methane, characterized in that It is prepared by the method according to any one of claims 1 to 11.

13. The catalyst according to claim 11, characterized in that: Calculated on the basis of the catalyst mass, the chlorine content is 0.001%-0.05%, and the active metal content is 3%-8%.

14. Use of a catalyst prepared by the method according to any one of claims 1 to 11 or a methane catalytic combustion catalyst according to any one of claims 12 to 13.

15. The use according to claim 14, characterized in that: At a volume space velocity of 10000 h -1 ~30000h -1 , under the condition of methane volume concentration of 1% to 3.5%, T 90 ≤500℃.

Citation Information

Patent Citations

  • Alkaline earth metal / metal oxide supported catalysts

    CN105188915A

  • Perovskite type honeycomb integral methane catalytic combustion catalyst and preparation method thereof

    CN106944093A

  • Epitaxial interface coupled metal oxide / perovskite composite catalyst and application thereof

    CN111715228A

  • Perovskite honeycomb monolithic methane catalytic combustion catalyst and preparation method thereof

    CN114870863A

  • Catalytic membrane reactor

    FR2879185A1

Cited By

  • Palladium-based monolithic catalyst and preparation and application thereof

    CN120695846A